Stopping bDMARDs at the beginning of pregnancy is associated with disease flares and preterm delivery in women with rheumatoid arthritis - Gerardi, Maria Chiara; Crisafulli, Francesca; García-Fernandez, Antía; Lini, Daniele; Bazzani, Chiara; Cavazzana, Ilaria; Filippini, Matteo; Fredi, Micaela; Gorla, Roberto; Lazzaroni, Maria Grazia; Nalli, Cecilia; Taglietti, Marco; et al. (Frontiers in Pharmacology, 2022)
Objectives: Women with Rheumatoid Arthritis (RA) can experience flares during pregnancy that might influence pregnancy outcomes. We aimed at assessing the disease course during pregnancy and identifying risk factors for flares. Methods: Data about prospectively-followed pregnancies in RA were retrospectively collected before conception, during each trimester and in the post-partum period. Clinical characteristics, disease activity (DAS28-CRP3), medication use, and pregnancy outcomes were analysed with regard to disease flares. Results: Among 73 women who had a live birth, 64 (88%) were in remission/low disease activity before conception. During pregnancy, a flare occurred in 27 (37%) patients, mainly during first and second trimester. Flares during pregnancy were associated with the discontinuation of bDMARDs at positive pregnancy test (55% of patients with flare vs 30% of patients with no flare, p 0.034, OR 2.857, 95% CI 1.112-8.323) and a previous use of >1 bDMARDs (33% of patients with flare vs 10% of patients with no flare, p 0.019, OR 4.1, 95%CI 1.204-13.966). Preterm pregnancies were characterised by higher values of CRP (10 mg/L [5-11] vs 3 mg/L [2.5-5], p 0.01) and DAS28-CRP3 (4.2 [1.9-4.5] vs 1.9 [1.7-2.6], p 0.01) during the first trimester as compared with pregnancies at term. Preterm delivery was associated with the occurrence of flare during pregnancy (flare 27% vs no-flare 7%, p 0.034, OR 4.625, 95%CI 1.027-20.829). Conclusion: Preterm delivery in RA patients was associated with flares during pregnancy. Flares occurred more frequently after the discontinuation of bDMARDs at positive pregnancy test. Women with aggressive RA on treatment with bDMARDs should be considered as candidates for continuing bDMARDs during pregnancy in order to reduce the risk of flare and adverse pregnancy outcomes.